System modeling in cell biology : from concepts to nuts and bolts - Szallasi, Zoltan; Stelling, Jörg; Periwal, Vipul (MIT Press, 2006)
This is an introduction and overview of system modelling in biology that is accessible to researchers from different fields including biology, computer science, mathematics, statistics physics, and biochemistry.